Postural control influence on upper extremity function among children with cerebral palsy: a literature review - Nur Zaidah Zulkapli; Nur Zakiah Mohd Saat; Sazlina Kamaralzaman (Penerbit Universiti Kebangsaan Malaysia, 2016)
Performance of upper extremity function and movement sequence is influenced by postural control. Motor disorders lead to deficits in postural control, which subsequently may lead to postural instability of children with cerebral palsy (CWCP). This will limit their upper extremity activity performance. Management strategies help to support and enhance the CWCP’s upper extremity function so that they may engage with the activities of daily living. The purpose of this paper is to review previous literature on the influence of postural control towards upper extremity function. Literature searches were conducted in various electronic databases, including ProQuest, Science Direct, Springer Link, Sage, Wiley Online Library, and Google Scholar using specific key terms. Search terms included children with cerebral palsy; postural control; postural adjustments; upper extremity function; reaching and sitting and from references of retrieved articles. Nineteen journal articles published between 2000 and May 2015 were found. Most search results consisted of experimental studies, while others are reviews, case studies, and cross-sectional studies. Findings show that, postural control has a major influence on upper extremity function. In conclusion, it is necessary to highlight the importance of both factors to the CWCP parents or caregivers, as understanding and awareness on this matter is still inadequate in the community. Hence, a study is needed on the awareness of the postural control influence on upper extremity function among caregivers, as well as examining the implementation of management strategies in community settings.